The Effectiveness Of Mini-games Training To Increase Motivation (cognitive-achievement-activation) To Learn Passing Skills - Nabi Mohamed Nadjh .; Bchir Houssame . (sports creativity, 2025)
Summary: Through our research, we try to suggest a learning style with Mini Games to increase motivation of 13-14 years players; we want to improve the capacities of passing balls from previously required bases. The are three sorts of motivation stated: cognitive, Achievement and activation motivation (internal motivation) .Our study requires 2 groups witness and experimental, we distributed randomly 12 players for each and both are subjected to anthropometric measurements in the same age, height, weight, and sex. For the experimental group, we applied a programme based on single game; whereas we only keep the previously used programme for the other group. Many statistically difference factors have been noticed in the psychological factor during the (post- test ) it was in the favor of the experimental sample. Therefore, it is obviously noticed that Mini Games have proved their effectiveness in increasing the level of motivation with the help of motivational terms by which the coach call his players during the training, it's so important through this stage of age . Key words: - Mini-games – Internal stimulation – passing skill – football and age characteristics. ا .